Experience of physical, emotional and sexual violence and adverse health behaviours in Macedonian students: results from the adverse childhood experience survey. (1st March 2011) - Raleva, M; Pesevska, D J; Sethi, D; Hadzihamza, K; Filov, I; Boskovska, M
Abstract : Objective: To examine associations between experience of physical violence, sexual violence and emotional violence and adverse health behaviours among a sample of students in Republic of Macedonia. Methods: In a cross-sectional analysis of data from high school and university survey in Republic of Macedonia educational institutions that participated in the adverse childhood experience survey in 2009–2010 we compared the relative frequency of several adverse health behaviours among students (primarily students 18–20 years of age) who did or who did not report experience of PV, SV or EV. We estimated ORs for such behaviours and theirs 95% CIs after adjusting for age and sex. Findings: Experience of physical violence in childhood was reported by 25–32% of the students studied in several regions in Macedonia, and experience of sexual violence was reported by 9–12%. Emotional abuse was reported by 37–43%. Moderate to strong associations were observed between adverse childhood experience of physical violence and sexual violence and measures of mental health, suicidal ideation, cigarette smoking, alcohol or substance abuse, multiple sex partners. Conclusion: Childhood experience of physical violence, emotional violence and sexual violence is common among Macedonian students and is associated with multiple adverse health behaviours. In developing country such as Macedonia, increased awareness of the frequency of experience of violence among children and its potential adverse health consequences may lead to heightened attention to the need for preventive programmes that address the problem.